Age and composition of Antarctic bedrock reflected by detrital zircons, erratics, and recycled microfossils in the Prydz Bay-Wilkes Land-Ross Sea-Marie Byrd Land sector (70 degrees-240 degrees E) - Veevers, J. J.; Saeed, Ayesha (Gondwana Research, 2011)
The age and composition of the 14x 10(6) km(2) of Antarctica's surface obscured by ice is unknown except for some dates on detrital minerals. In remedy, we bring together proxies of Antarctic bedrock in the form of (1) detrital zircons analysed for U-Pb age, T-DM(C), epsilon Hf, and rock type, including five new analyses of Neogene turbidites, (2) erratics that reflect age, composition, and metamorphism, and (3) recycled microfossils that reflect age, facies, and metamorphism. Each sample is located in its ice-drainage basin for backtracking to the potential provenance. Gaps in age between sample and upslope exposure are specifically attributable to the provenance. This work indicates that the central Antarctic provenance about a core of the Gamburtsev Subglacial Mountains (GSM) and Vostok Subglacial Highlands (VSH) contains a basement that includes igneous (mafic granitoids) and metamorphic rocks with peak U-Pb ages of 0.5-0.7, 0.9-1.3, 1.4-1.7, 1.9-2.1, 2.2-2.3,2.6-2.8, and 3.15-3.35 Ga, T-DM(C) 1.3-3.6 Ga, and epsilon Hf + 12 to 40. Other modelled cratons with similar ages are set in a matrix of foldbelts of 0.5-0.7 Ga age. The basement in the core is surmounted by Permian red beds, at the periphery by Permian and Triassic sedimentary rocks unaffected by igneous heating or load metamorphism, and west of the Transantarctic Mountains (TAM) in the Wilkes Basin arguably by Late Cretaceous through Pliocene marine sediments. Erratics of undated red sandstone along the coast of Wilkes Land and George V Land indicate a red-bed provenance in the interior. The Prince Charles Mountains (PCM) provide an exposed example of a crust of Precambrian igneous and metamorphic rocks and Permian and Triassic sedimentary rocks. (C) 2011 International Association for Gondwana Research. Published by Elsevier B.V. All rights reserved.